Review of an Accurate System Utilizing GPS Technology - Nadia Mahmood Hussien; Yasmin Makki Mohialden; Basim K. Abbas; Itidal Saad Mohammed (Newinera Publisher, 2022)
GPS provides precise position and control data anywhere on the planet and in any weather condition. GPS was originally intended for military usage, but in the 1980s, the US Department of Defense made it available for civilian use. The scientific applications of GPS in the military, community, and commercial sectors are expanding on a regular basis. Agriculture, construction, mining, measurement, package delivery, and logistical supply chain management all benefit from GPS technology. Precision GPS time synchronization is critical for big networks, navigation, finance systems, financial markets, and power grids. Wireless services are impossible to imagine without them. In this paper, we will go over the key aspects of GPS technology as well as a discussion of the systems that use it.